2021
DOI: 10.1155/2021/4194859
|View full text |Cite
|
Sign up to set email alerts
|

Increased IgE Deposition in Appendicular Tissue Specimens Is Compatible with a Type I Hypersensitivity Reaction in Acute Appendicitis

Abstract: Background. IgE mediates type I hypersensitivity reaction and can be found in the mucosa of organs affected by allergy. Acute appendicitis (AA) is a common disease, but its etiology remains poorly understood. Here, we investigated IgE deposition in histological sections of AA samples to test the hypothesis that an allergic reaction may substantially contribute to the pathophysiology of AA. Materials and Methods. In a retrospective study, we assessed the presence of IgE in appendicular specimens of histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(49 citation statements)
references
References 27 publications
3
46
0
Order By: Relevance
“…The lower number of eosinophils was detected in AGA. When we analysed the presence of IgE in the walls of AA specimens, a similar distribution of intensity was reported [ 6 ].…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The lower number of eosinophils was detected in AGA. When we analysed the presence of IgE in the walls of AA specimens, a similar distribution of intensity was reported [ 6 ].…”
Section: Discussionsupporting
confidence: 62%
“…Some contemporary insights suggest that allergy may be an important player in AA [ 3 , 4 ]. Recent and ongoing results of our group corroborate this line of research [ 5 , 6 ] and allergy was searched for as the “missing link” in the aetiology of AA [ 7 ]. If, in this narrative revision [ 7 ], a definitive causal relation between allergy and acute AA could not be established, it was well stated that allergic features are undoubtedly present in AA [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Based on this hypothesis, we conducted our previous studies on the association between (the Th2 associated) IgE-mediated allergy and a lower risk of complicated appendicitis ( 15 , 16 ), which have now been continued in the present study through measurement of the IgE-levels. Previous studies from other authors have found a significant increase in IgE deposits in phlegmonous appendices compared to incidentally removed appendices, but not compared to gangrenous appendicitis and negative appendectomies ( 17 ). Furthermore, two studies have reported significant associations of eosinophilia and uncomplicated appendicitis in children ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 80%